Cash thresholds, cash expenditure and tax evasion. (19th December 2022) - Russo, Francesco Flaviano
Abstract: Using data for Italy, I show that cash thresholds that forbid the use of cash for big transactions are effective tools to reduce cash income and cash circulation. Less cash income, in turn, hinders tax evasion. I present an estimate of the increase in tax revenue implied by the empirically estimated reduction of cash income determined by the thresholds.